α1-nAchR-Mediated Signaling Through Lipid Raft Is Required for Nicotine-Induced NLRP3 Inflammasome Activation and Nicotine-Accelerated Atherosclerosis - Duan, Fengqi; Zeng, Cheng; Liu, Sijun; Gong, Jianfeng; Hu, Jia; Li, Hongyu; Tan, Hongmei (Frontiers in Cell and Developmental Biology, 2021)
Backgroud Nicotine exerts direct effects on multiple cell types in the cardiovascular system by associating with its high-affinity nicotinic acetycholine receptors (nAchRs). Lipid raft is membrane microdomain which recruits various receptors and signaling molecules for coordinating cellular immune response and many others signaling processes. Here we aim to identify the essential role of lipid raft in mediating nicotine-triggered inflammatory and -accelerated atherosclerosis, and to figure out the specific receptor of nicotine-induced Nod-like receptor protein 3 (NLRP3) inflammasome activation in macrophage. Methods and results ApoE-/- mice were fed with a high fat diet to build atherosclerosis model. Methyl-β-cyclodextrin was used to interrupt intact lipid raft. We confirmed that nicotine triggered NLRP3 inflammasome activation and induced macrophage migration into atherosclerotic plaque, thus accelerated atherosclerosis in apoE-/- mice fed with a high fat diet. Mechanically, nicotine increased the expression of α1-nAChR and stimulated the accumulation of α1-nAChR in lipid raft, leading to NLRP3 inflammasome activation in macrophage. Conversely, silencing of α1-nAChR in macrophage sufficiently blocked the pro-inflammasome activation effect of nicotine, indicating that α1-nAChR was the specific receptor for nicotine in triggering NLRP3 inflammasome in macrophage. Furthermore, both the destruction of lipid raft by methyl-β-cyclodextrin and the interference of lipid raft clustering by silencing acid sphingomyelinase reversed nicotine-induced NLRP3 inflammasome activation by reducing the accumulation of α1-nAChR in lipid raft in macrophage, suggesting lipid raft mediated accumulation of α1-nAChR was the key event in regulating the pro-inflammatory effects of nicotine in macrophage. Importantly, nicotine-induced NLRP3 inflammasome activation and macrophage migration into atherosclerotic plaque were reversed by methyl-β-cyclodextrin, making a significant improvement for atherosclerosis in apoE-/- mice fed with a high fat diet. Conclusions α1-nAChR-mediated signaling through lipid raft is required for NLRP3 inflammasome activation and pro-atherosclerotic property of nicotine.